Perdagangan Manusia (Human Trafficking) sebagai Kejahatan Internasional: Upaya Pemberantasan dan Penegakan Hukum - Muhammad Dede Al Farabi Suardi; Denis Salwani; Ariel Lian Pratama Reksa (CV. ITTC INDONESIA, 2026)
Human trafficking is a serious transnational crime that violates human rights by treating individuals as commodities. Under the Palermo Protocol, this crime encompasses the recruitment, transportation, and harboring of persons through illegal means for exploitative purposes, including forced labor and sexual exploitation.This article examines the qualification of human trafficking as an international crime and analyzes law enforcement efforts under both international law and Indonesian Law No. 21 of 2007, using a normative juridical approach.The study concludes that human trafficking is cross-border in nature, highly organized, and poses a broad threat to human security. Despite ongoing efforts in prevention, victim protection, and prosecution, implementation remains hindered by low public awareness, weak inter-state coordination, and increasingly sophisticated digital crime methods. Stronger synergy among the state, law enforcement, and society is essential to ensure effective law enforcement and optimal protection for victims.